Inhibition of Iron Absorption by Calcium Is Modest in an Iron-Fortified, Casein- and Whey-Based Drink in Indian Children and Is Easily Compensated for by Addition of Ascorbic Acid. Issue 11 (3rd September 2014) - Walczyk, Thomas; Muthayya, Sumithra; Wegmüller, Rita; Thankachan, Prashanth; Sierksma, Aafje; Frenken, Leon G. J.; Thomas, Tinku; Kurpad, Anura; Hurrell, Richard F.
Abstract: Background: Calcium inhibits and ascorbic acid (AA) enhances iron absorption from iron-fortified foods. Absorption efficiency depends on iron status, although the interaction is unclear. Objective: We investigated the ability of AA to overcome calcium-induced inhibition of iron absorption in children differing in iron status. Methods: The effect of calcium (0, 100, and 200 mg/test meal) on iron absorption in the absence and presence of AA (0, 42.5, and 85 mg/test meal) from a casein/whey-based drink fortified with ferrous sulfate was assessed in a series of randomized crossover studies both in iron-replete (IR) Indian schoolchildren and in children with iron deficiency anemia (IDA) (6–11 y; n = 14–16/group) by using stable isotopes. Results: In the absence of calcium and AA, iron absorption from the casein/whey-based drink was 20% lower in IR children than in children with IDA. The addition of calcium reduced mean iron absorption by 18–27%, with the effect being stronger for high added calcium ( P < 0.01). AA at a 2:1 or 4:1 molar ratio enhanced iron absorption by a factor of 2–4 and greatly overcompensated for the inhibitory effect of calcium on iron absorption in a dose-dependent manner ( P < 0.001). The dose-response effect tended to be stronger ( P < 0.1) in the IDA group, and iron status was of far less influence on iron absorption than the enhancing effect of AA. Conclusion: When adding AA to iron-fortified milk products, care should be taken not to provide absorbable iron in excess of needs.